An ACOA-AFSA Fusion Routing Algorithm for Underwater Wireless Sensor Network - Huafeng Wu; Xinqiang Chen; Chaojian Shi; Yingjie Xiao; Ming Xu (International Journal of Distributed Sensor Networks)
Due to intrinsic properties of aqueous environments, routing protocols for underwater wireless sensor network (UWSN) have to cope with many challenges such as long propagation delay, bad robustness, and high energy consumption. Basic ant colony optimization algorithm (ACOA) is an intelligent heuristic algorithm which has good robustness, distributed computing and combines with other algorithms easily. But its disadvantage is that it may converge at local solution, not global solution. Artificial fish swarm algorithm (AFSA) is one kind of intelligent algorithm that can converge at global solution set quickly but has lower precision in finding global solution. Therefore we can make use of AFSA and ACOA based on idea of complementary advantages. So ACOA-AFSA fusion routing algorithm is proposed which possesses advantages of AFSA and ACOA. As fusion algorithm has aforementioned virtues, it can reduce existing routing protocols' transmission delay, energy consumption and improve routing protocols' robustness theoretically. Finally we verify the feasibility and effectiveness of fusion algorithm through a series of simulations.